The Role of ICT in Learning Processes and University Inclusion - Antonelli, Carlotta (Community Notebook. People, Education and Welfare in the Society 5.0, 2023)
The proposal presents the first outputs of the Universitabile doctoral thesis based on the relationship between educational inclusion (Ainscow and Miles, 2009) and ICT. Using a mixed methods approach, the paper analyses interviews administered to operators of dedicated services, exploring the issue of barriers and facilitation mechanisms during the Covid-19 emergency, presenting technology as an element of exclusion.